Effects of hydrogen direct injection on combustion and emission characteristics of a hydrogen/Acetone-Butanol-Ethanol dual-fuel spark ignition engine under lean-burn conditions. (27th November 2020) - Yu, Xiumin; Li, Decheng; Yang, Song; Sun, Ping; Guo, Zezhou; Yang, Hang; Li, Yinan; Wang, Tianqi
Abstract: Acetone-Butanol-Ethanol (ABE) is an essential product in the production process of butanol, which is considered as an effective way to replace butanol used in engines because of the lower production cost of ABE. Hydrogen is an ideal fuel for engines because of its low ignition energy and high flame propagation speed. In this study, the effects of hydrogen addition on the combustion and emission characteristics of a spark ignition ABE engine under lean-burn conditions are investigated. Specifically, five hydrogen blending ratios (0, 5%, 10%, 15%, 20%) and three λ values (1, 1.1, 1.2) are studied. The results show that adding hydrogen can increase the maximum cylinder temperature and pressure, decrease the flame development and propagation duration of the hydrogen/ABE dual-fuel SI engine. In addition, hydrogen addition can reduce the COVIMEP, BSFC, CO, HC emissions, and improve the IMEP, but increase NOx emissions; however, a lower NOx emissions for the hydrogen/ABE engine working under learn-burn conditions (λ equals 1.2) can be achieved with a suitable proportion of hydrogen adding (proportion = 5%) than that of engine working under stoichiometric air-fuel ratio condition. Thus, hydrogen addition can facilitate the combustion of ABE in engines, especially under lean-burn conditions. Highlights: Hydrogen optimized the Acetone-Butanol-Ethanol combustion. The combustion duration reduced after hydrogen addition. Hydrogen improved COVIMEP and operation stability. Hydrogen improved the engine both power performance and economy. Hydrogen addition improved the CO and HC emissions.